In situ micro-scale high-speed imaging for evaluation of fracture propagation and fracture toughness of thermoplastic laminates subjected to impact. (15th February 2019) - Wafai, H.; Yudhanto, A.; Lubineau, G.; Mulle, M.; Alghamdi, T.; Thoroddsen, S.T.; Yaldiz, R.; Verghese, N.
Abstract: Measuring parameters related to each damage mode of composites subjected to impact is very challenging because of the complex damage phenomenology. Here, we developed an experimental methodology for evaluating the micro-scale fracture characteristics of two principal damage modes, i.e., transverse crack and delamination, and providing the corresponding fracture toughness. We demonstrated the capability of the method by comparing and providing additional insights about two materials, namely homopolymer-based (ductile) and copolymer-based (less-ductile) glass/polypropylene thermoplastic composites. We found that (i) transverse crack behavior of both composites is similar as indicated by a small difference in their fracture toughness, (ii) delamination growth in copolymer-based composites is slower than in homopolymer-based composites, (iii) the fibrillation induced by rubber particles in copolymer-based composites is responsible for decelerating the delamination growth and improving its fracture toughness during delamination. This method is deemed useful and quick for determining the micro-scale fracture behavior of composite laminates under impact in order to support the material selection process.